UV reflectance but no evidence for colour mimicry in a putative brood-deceptive orchid Corybas cheesemanii. Issue 1 (1st February 2014) - Kelly, M. M.; Gaskett, A. C.
Abstract: Rewardless orchids attract pollinators by food, sexual, and brood-site mimicry, but other forms of sensory deception may also operate. Helmet orchids ( Corybas, Nematoceras and related genera) are often assumed to be brood-site deceivers that mimic the colours and scents of mushrooms to fool female fungus gnats (Mycetophilidae) into attempting oviposition and pollinating flowers. We sampled spectral reflectances and volatile odours of an endemic terrestrial New Zealand orchid Corybas cheesemanii, and co-occurring wild mushrooms. The orchid is scentless to humans and SPME GC-MS analyses did not detect any odours, but more sensitive methods may be required. The orchids reflected strongly across all visible wavelengths (300-700nm) with peaks in the UV (~320nm), yellow-green (500-600 nm) and red regions (650-700 nm), whereas mushrooms and surrounding leaf Utter reflected predominantly red and no UV. Rather than mimicking mushrooms, these orchids may attract pollinators by exploiting insects' strong sensory bias for UV. Modelhng spectral reflectances into a categorical fly vision model and a generic tetrachromat vision model provided very different results, but neither suggest any mimicry of mushrooms. However, these models require further assessment and data on fly spectral sensitivity to red wavelengths is lacking – a problem given the predominance of red, fly-pollinated flowers worldwide.